ECONOMIC ANALYSIS OF CATFISH FARMING AND ITS CONTRIBUTIONS TO HOUSEHOLD POVERTY ALLEVIATION IN ANAMBRA STATE, SOUTH EAST NIGERIA - Njideka Rita , Chiekezie,; Eucharia C, Nwankwo; Maurice. Uche, Ozor (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
The study analyzed factors influencing the potency of catfish farming determined the cost and returns of catfish farming, estimated the poverty status among catfish farmers and ascertained the contribution of catfish farming to household poverty alleviation in the study area. Primary data used for the study was collected using well-structured questionnaire which was administered to sampled Catfish farmers in the study area. In analyzing the data, descriptive statistical tools (frequency counts, means and percentages), enterprise budgeting techniques, Tobit regression model, expenditure approach of determining poverty line, Foster, Greer and Thorbecke technique and z-test were used. The results indicated that factors such as pond size (0.0004), feed (0.6411), labour (-0.0003), and farming experience (0.0105) had influence on potency of catfish farming . Net returns analysis result reveals a return on investment of ?1.51 and it implies that the catfish production enterprise generated 1.51 times more income than expenses incurred for the production, a gross ratio of 66% and a Profitability Index (PI) of 0.34 which means that for every naira earned as revenue, 0.34kobo was returned to the farmer as net income. This result surely indicates that cat fish production is highly lucrative in the study area. At 0.05 probability level, the calculated z value was statistically significant and thereby ascertained the positive contribution of catfish farming to household poverty alleviation. Based on this study, the following recommendations are made: Since catfish production are profitable, government need to devote more resources to the catfish farmers to ensure that the best practices are adopted for further sustainability of the agribusiness, farmers should be trained on how to compound different types of fish feed to enable them reduce cost of feed. In addition Government should ensure increased credit facilities by the financial institutions to enable the farmers spread out their scale of operation